The Determinant of Vitamin D Adequacy in Fishermen - Irawati, Deasy; Ekawanti, Ardiana; Nurbaiti, Lina (Jurnal Kedokteran, 2020)
Background: The prevalence of vitamin D deficiency in both developed and developing countries are 30% - 75% with increased risk reported among women, elderly, obese individuals and those with low sun exposure. Fisherman has been acknowledged as an occupation with high sun exposure. However, a previous study showed that 4 in 5 fishermen were vitamin D deficient. The objective of this study is to investigate vitamin D intake and sun exposure among fishermen. Method: This cross-sectional study recruited fishermen residing in the working area of several public health centres in Mataram and West Lombok districts. The subjects were classified as fishermen and non-fishermen. Vitamin D intake and sun exposure were the the main variables. Results: One in two fishermen and three in four non-fishermen exhibited low intake of vitamin D. Fish intake in the fisherman and the non-fisherman groups were 937 gram per week and 652 gram per week, respectively. The most consumed fish was tuna. Fish intake of 937 gram per week was equivalent to ~12 Âµg vitamin D intake and 23.6 nmol/L vitamin D concentration. The majority of subjects were unable to achieve the optimal UVB radiation. Conclusion: Insufficient vitamin D intake and limited sun exposure are prevalent in fisherman and non-fisherman groups.